Primary cardiac hydatid cyst presenting as noncompaction cardiomyopathy. Issue 1 (30th September 2016) - Kocabay, Gonenc; Yilmazer, Serdar; Korkmaz, Yetkin; Karadeniz, Asli; Duran, Nilufer Eksi
Abstract : We report a case of cyst was initially labeled as left ventricular noncompaction cardiomyopathy. An accurate diagnosis is essential to establish the most effective treatment strategy. In particular, echocardiographic examination assists in identifying the correct diagnosis. In this case, two‐dimensional and three‐dimensional echocardiography and computed tomography were used for definitive diagnosis of cardiac hydatid cyst.